ANTECEDENTS OF INTERNAL COMMUNICATION SUCCESS IN PUBLIC ORGANIZATIONS : A STUDY OF HIGH PROSECUTOR'S OFFICE OF SOUTH SUMATRA - Dandi Putratama; Anang Dwi Santoso; Erlisa Saraswati (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2025)
Using a case study of the High Prosecutor's Office of South Sumatra, this study seeks to determine and demonstrate the factors that contribute to the success of internal communication. Using SmartPLS software, this study applies partial least square structural equation modeling (SEM-PLS) on a sample of 77 employees. According to the findings of this study, the success of internal communication at the South Sumatra High Court is determined by professional communication, the channels utilized in internal communication, and employee participation in using media channels. The practical implication of this study is that to increase the success of internal communication, the South Sumatra High Prosecutor's Office must improve professional communication with employees so that they can participate with leaders in decisions regarding the organization's internal communication strategy, and increase the use of communication channels utilized by employees.